The Emerging Roles of the β-Secretase BACE1 and the Long Non-coding RNA BACE1-AS in Human Diseases: A Focus on Neurodegenerative Diseases and Cancer - Sayad, Arezou; Najafi, Sajad; Hussen, Bashdar Mahmud; Abdullah, Sara Tharwat; Movahedpour, Ahmad; Taheri, Mohammad; Hajiesmaeili, Mohammadreza (Frontiers in Aging Neuroscience, 2022)
The -secretase (BACE1) is widely studied to be particularly involved in amyloid deposition; a process known as the pathogenic pathway in neurodegenerative diseases. Therefore, BACE1 expression is frequently reported to be upregulated in brain samples of Alzheimer’s disease patients. BACE1 expression is regulated by BACE1-AS; a lncRNA which is transcribed in opposite direction to its locus. BACE1-AS positively regulates the BACE1 expression, their expression levels are regulated playing role in physiological processes like brain and vascular homeostasis; although their roles in regulation of amyloidogenic process have been studied further. BACE1-AS dysregulation is reported consistent with BACE1 in a number of human diseases like Alzheimer’s disease, Perkins’s disease, heart failure, and mild cognitive impairment. BACE1 or less BACE1-AS inhibition have shown therapeutical potentials particularly in decreasing manifestations of amyloid-linked neurodegenerative diseases. Here, we have reviewed the role of lncRNA BACE1 and BACE1-AS in a number of human diseases focusing on neurodegenerative disorders particularly Alzheimer’s disease.